Implementasi Sistem Manajemen Mutu ISO 9001:2015 Untuk Pencapaian Kinerja Unggul di Organisasi - Syaipul Bachren; Trisninawati, Trisninawati (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the role of implementing the ISO 9001:2015 Quality Management System in achieving superior organizational performance measured through the Baldrige Excellence Framework (BEF). The research employs a qualitative literature review approach, examining scientific and official standard sources from 2021 to 2025. Data analysis is carried out descriptively and critically, evaluating the alignment of ISO 9001:2015 principles—such as the process approach, Plan-Do-Check-Act (PDCA) cycle, and risk-based thinking—with BEF performance assessment categories including leadership, strategy, customers, workforce, operations, and results. Findings indicate that organizations consistently implementing quality management systems better satisfy BEF criteria, significantly enhancing operational efficiency, customer satisfaction, and competitiveness. The integration of ISO 9001:2015 with BEF also fosters a strong culture of continuous improvement and innovation within organizations. The study concludes that a structured, in-depth Quality Management System serves as an effective strategy for organizations aiming to thrive and excel amid dynamic, complex business environments.